TINJAUAN YURIDIS KEWAJIBAN KETERBUKAAN INFORMASI PANITIA SELEKSI PERANGKAT DESA MENURUT UU PELAYANAN PUBLIK - Syahrian; Muhammad Aini (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the legal standing of the village apparatus selection committee as a public service provider and to examine the legal construction of information disclosure obligations in the recruitment process based on Law Number 25 of 2009 concerning Public Services. The research method used is normative juridical with a statute approach and a conceptual approach. The results indicate that the village apparatus selection committee normatively qualifies as a public service provider in the village government administration sector, fully bound by the principles of public service. The obligation of information disclosure includes transparency of assessment standards, exam results, and the provision of a public objection mechanism. Information concealment in technical regulations at the regional level (Regent Regulation) that stifles selection transparency can be categorized as a normative legal defect because it violates the principle of lex superior derogat legi inferior against the Public Service Law.